2006
DOI: 10.1149/ma2005-01/13/591
|View full text |Cite
|
Sign up to set email alerts
|

In Search Of Higher Density MIM Capacitor forGaAs RF Applications

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…The reduction of the die size can be achieved by reducing the area of circuit components in the designs. One such component is the metal-insulator-metal (MIM) capacitor, which is a key passive device in GaAs technology (1)(2)(3)(4)(5). The MIM capacitor area in the designs can be reduced by increasing the capacitance density, which can be achieved by using a higher dielectric constant material as the capacitor dielectric.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduction of the die size can be achieved by reducing the area of circuit components in the designs. One such component is the metal-insulator-metal (MIM) capacitor, which is a key passive device in GaAs technology (1)(2)(3)(4)(5). The MIM capacitor area in the designs can be reduced by increasing the capacitance density, which can be achieved by using a higher dielectric constant material as the capacitor dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative that the capacitor dielectric material used to fabricate the MIM capacitor has high dielectric constant and capacitance density. Furthermore, the MIM capacitor dielectric in many GaAs circuit designs also has to have high breakdown voltage, as many of these designs that are fabricated using GaAs technologies, including hetero-junction bipolar transistor (HBT) technology, have typically high operating voltage and have transistor output voltage swings that can be 20 V or higher (2,3,6,7). In addition to high breakdown, the MIM capacitor in most GaAs designs and applications also has to have low leakage current, especially when the device operates at high voltage and high temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal-insulator-metal capacitors has thus become a key building block for mixed signal applications as it offers low parasitic capacitance, especially when fabricated on metal 2 or higher, as well as good linearity since the both electrodes are made of metal. Previous studies demonstrated that because of the higher dielectric constant of the PECVD nitride compare to oxide (5), nitride allows a higher capacitance for the same thickness of the dielectric. This makes it the most popular layer used as MIMC dielectric.…”
Section: Introductionmentioning
confidence: 99%